A new Interpolatory Model Reduction Approach for Quadratic Bilinear Descriptor Systems. Issue 1 (21st October 2015) - Ahmad, Mian Ilyas; Benner, Peter; Feng, Lihong
Abstract: We propose interpolation based projection techniques for model reduction of quadratic bilinear descriptor systems. The approach identifies projection matrices from the bilinear approximation of the original quadratic bilinear descriptor system and applies Petrov‐Galerkin projection to the original system to construct the required reduced quadratic bilinear descriptor system. Two different techniques of computing the projection matrices from the bilinear approximation are proposed. One is based on linear parametric model reduction and the other is the bilinear rational Krylov method. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)